Analytical fin efficiency model for open-cell porous metal fins based on Kelvin cell assumption. (1st November 2022) - Park, Sung-Ho; Jeong, Ji Hwan
Highlights: Open-cell porous metal was represented by a polyhedron model known as the Kelvin cell. Analytical fin efficiency model for open-cell porous metal was derived. Analytical model is in good agreement with the fin efficiency evaluated using CFD. Abstract: Open-cell porous metals are widely used to enhance convective heat transfer of thermal management devices. In this paper, the open-cell porous metal structure was represented by a polyhedron model known as the Kelvin cell, and an analytical model for the efficiency of the porous metal fin attached to an isothermal surface was derived. The forced convective heat transfer coupled with heat conduction through the ligaments of porous metal was analyzed to derive the fin efficiency model. The effects of pore diameter, ligament diameter, and porous metal fin height on the fin efficiency and heat transfer rate of porous metal fins were also investigated. The new analytical fin efficiency model based on the Kelvin cell was compared with the fin efficiency evaluated using computational fluid dynamics analysis results; good agreement was found. The proposed analytical fin efficiency model avoids the numerical calculations required for heat transfer analysis of porous metals used as extended surfaces in many engineering applications such as heat sinks and heat exchangers, and can produce simple but effective results.